Lepanthes aures-ursinae and L. vertebrata spp. nov. (Orchidaceae: Pleurothallidinae) from Panama - Bogarín Chaves, Diego Gerardo (2017)
Panama is still far from completing its orchid flora inventories, where large genera such as Lepanthes (Pleurothallidinae) reveal novelties regularly. Here, we describe and illustrate two new species of Lepanthes. Lepanthes aures‐ursinae is similar to L. micellilabia but differs by the orbicular‐ovate, obtuse, convex leaves, larger sepals 2.7–3.0 × 2.2–2.3 mm the yellow petals, shorter column to 1 mm long and Y‐shaped bi‐laminate lip with the blades embracing the column and the body elongated towards the base of the column forming a cylindric structure. Lepanthes vertebrata is most similar to L. demissa, from which it can be distinguished by the inflorescences bearing 20–73 pedicels in well‐developed inflorescences, the vinaceous flowers, the larger lateral sepals to 6.0 × 2.3 mm, wider petals to 4.5 mm with the lower lobe longer than the blades of the lip, narrowly oblong upper lobe of petals, oblong lower lobe, shorter lip ca 1 mm long with ovate pink blades and ventral stigma. Data on distribution, habitat and ecology, etymology and phenology are provided for each species.